Hemostatic Wound Dressing for Postinterventional Hemostasis in Large Femoral Artery Access Sites: An Initial Efficacy and Safety Study. (October 2016) - Sauer, Alexander; Dierks, Alexander; Wolfschmidt, Franziska; Hassold, Nicole; Bley, Thorsten A.; Kickuth, Ralph
Purpose: To present the results of a prospective single-center study that evaluated the safety and efficacy of a hemostatic dressing following femoral artery access.Methods: Within a 9-month period, 80 patients (mean age 68±14 years; 55 men) were treated with a hemostatic dressing patch (Hematrix Active Patch) containing aminocaproic acid, calcium chloride, and thrombin after endovascular procedures via a 6- to 8-F femoral artery access. After removing the sheath, the wound dressing was placed on the puncture site followed by constant manual compression adapted to the sheath size (specified pressure times: 8 minutes for 6-F, 9 minutes for 7-F, and 10 minutes for 8-F). Patients were treated with an additional pressure bandage for 24 hours. Hemostasis was checked clinically and with duplex ultrasound after patch removal and at 24 hours. Patient characteristics [platelets, systolic blood pressure, international normalized ratio (INR), and partial thromboplastin time (PTT)], sheath sizes, and approach direction were compared among patients with successful hemostasis (within specified pressure times) vs those with prolonged compression.Results: A total of 39 6-F, 19 7-F, and 22 8-F sheaths were employed. In 73 (91.2%) of 80 patients, hemostasis was reached within the prespecified pressure times (mean 8.8±0.8 minutes). In 7 patients (4 6-F, 1 7-F, 2 8-F) a longer compression time was necessary (mean 34±30 minutes). No serious major complication occurred. Twelve (15.0%) minor and 5 (6.3%) moderate subcutaneous hematomas were observed. Two (2.5%) false aneurysms were treated successfully. Ambulation and discharge was possible within 24 hours in 79 (98.7%) cases. Patients with initial hemostasis and those with prolonged compression did not differ substantially (p>0.05) according to sheath size, approach direction, INR (1.09±0.3 vs 1.11±0.3), platelets (234±47×10 3 /µL vs 249±93×10 3 /µL), systolic blood pressure (150±26 vs 152±17 mm Hg), or PTT (31±7.9 vs 34.8±10.0 seconds).Conclusion: The evaluated wound dressing seems to be safe and effective in reducing time to hemostasis in large arterial access sites. However, a randomized trial with a larger population and an active control group is necessary to confirm these preliminary data. Moreover, additional focus on shortening the time to ambulation is required in future studies.